2017
DOI: 10.1177/0093854817734278
|View full text |Cite
|
Sign up to set email alerts
|

The Financial Cost of a Criminal Conviction: Context and Consequences

Abstract: Growing fiscal concerns for criminal justice agencies and punitive ideological shifts have increased the financial consequences of a conviction. The growth in legal financial obligations (LFOs), such as fees, fines, and restitution resultant from conviction has important implications for offender reentry, particularly offender reintegration and opportunities for social advancement. Utilizing data culled from in-depth qualitative interviews with a sample of persons under correctional supervision, the current re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
65
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 45 publications
(78 citation statements)
references
References 37 publications
3
65
0
Order By: Relevance
“…First, because offenders tend to have few assets, they do not have the financial ability to pay the sanctions (Harris, ). As a result, they are more likely to experience the negative effects of nonpayment (Pleggenkuhle, ), including both criminal justice consequences (e.g., continuation on probation supervision and possible revocation) and financial consequences (e.g., impact on credit and limitations on employment). Second, these effects on credit, borrowing, housing, and employment may limit offenders’ successful reintegration into society (Harris, Evans, and Beckett, ).…”
Section: Imposition and Payment Of Economic Sanctionsmentioning
confidence: 99%
“…First, because offenders tend to have few assets, they do not have the financial ability to pay the sanctions (Harris, ). As a result, they are more likely to experience the negative effects of nonpayment (Pleggenkuhle, ), including both criminal justice consequences (e.g., continuation on probation supervision and possible revocation) and financial consequences (e.g., impact on credit and limitations on employment). Second, these effects on credit, borrowing, housing, and employment may limit offenders’ successful reintegration into society (Harris, Evans, and Beckett, ).…”
Section: Imposition and Payment Of Economic Sanctionsmentioning
confidence: 99%
“…LFO debts can cause long term debt and damaged credit (Harris et al, 2010;Pleggenkuhle, 2018), with one study reporting 75% sent to collections; African-Americans are more likely to have their debt sent to collections (Diller et al, 2009). Mixed and qualitative studies explore how people who owe LFO debts rely on social networks for financial support which causes family strain (Cook, Johnson, 2015;Nagrecha et al, 2015;Pleggenkuhle, 2012;Pogrebin, West-Smith, Walker, & Unnithan, 2014), forgo basic necessitates to make payments (Cook, 2014;Harris, 2016), face difficulties finding housing (Harris et al, 2010;Mogk, Shmigol, Futrell, Stover, & Hagopian, 2019), and are discouraged from entering formal economy or are forced to work low-wage jobs and forgo career-enhancing training/ education (Harris et al, 2010;Ortiz & Jackey, 2019;Pleggenkuhle, 2018). Various studies using different methods found that LFO debt may cause recidivism due to illegal activity or incarceration due to non-payment; two mixed methods studies found the latter happen in 17%-20% of cases (Cook, 2014;Ortiz, 2010;Ortiz & Jackey, 2019;Tostlebe, 2017).…”
Section: Scope and Impact Of Debtmentioning
confidence: 99%
“…Debt from LFOs, including bail, results in individuals and their familiesparticularly female family members -borrowing from costly, predatory lenders (Cook, 2014;Page et al, 2019), cutting back on essentials and falling behind on bills (Cook, 2014;Harris et al, 2010;Richards & Jones, 1997). LFO debt is associated with negative mental health including stress, a sense of hopelessness, feeling overwhelmed, and substance use (Arditti & Few, 2006;Cook, 2014;Harris, 2016;Pleggenkuhle, 2018).…”
Section: Scope and Impact Of Debtmentioning
confidence: 99%
See 1 more Smart Citation
“…The security situation in the security environment is influenced by many aspects. In regions, the security situation is mainly influenced by indicators of a socio-economic character [9]. These indicators can be aggregated according to common features into separate blocks.…”
Section: Security In Economic Developmentmentioning
confidence: 99%